Teaching and Hand-out Teaching Systems: a Critique Based on Habermas' Theory - Bego, Amadeu Moura [UNESP]; Terrazzan, Eduardo Adolfo; Andrade Oliveira, Luiz Antonio [UNESP] (Univ Metodista Piracicaba-unimep, 2015)
Because of the Brazilian State Management Reform and the vertiginous process of elementary school municipalization, several counties began to establish partnerships with the private sector. Among the partnership arrangements, the acquisition of Hand-Out Teaching Systems (HOTS) involves hiring companies for the purchase of teaching materials and didactic and pedagogical support. This work presents a critique based on Habermas' Theory about the main conditioning factors that act upon the teaching work regarding the use of HOTS. Thus, we performed a survey between years 2011 and 2012, with a Case Study qualitative approach about the Municipal School System of Catanduva, a town located in the state of Sao Paulo. The conditioning factors identified are the outsourcing of didactic work, the unification of the teaching work rhythm and external evaluations. The articulation of constraints implies the structuring and control of the teaching work, which tends toward the mere controlled execution of that which was preconceived and organized. To make the school aware of the problems arising from the systemic invasion of the lifeworld and the conditions attached to this process means creating a culture of resistance to the exacerbated insertion of technocracy in the institutional spaces of political decision, avoiding the one-sidedness of instrumental rationality.
Keywords: HAND-OUT TEACHING SYSTEMS; PUBLIC-PRIVATE PARTNERSHIP; RATIONALITY; HABERMAS